PENGARUH KERJASAMA TIM DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA GURU DI MADRASAH IBTIDAIYAH NEGERI (MIN) JAMBUR BARU KECAMATAN BATANG NATAL - SUWANDI PRATAMA HSB (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
The purpose of this study was to determine the effect of teamwork and work discipline on the effectiveness of teacher work at the Jambur Baru State Madrasah Ibtidaiyah (MIN) Batang Natal Distict. The population in this study were 32 teachers at Jambur Baru Elementary School (MIN) Batang Natal Distict. The result of this study are, the teamwork variable (X1) has tcount (5.123) > ttable (1.699) and significant (0.000) < 0.05. thus teamwork variable has a positive and significant effect on the work of teachers in Jambur Baru State Madrasah Ibtidaiyah (MIN) Batang Natal Distict. Work discipline variable (X2) has tcount (4.079) > ttable (1.699) and significant (0.000) < 0.05. Thus the work discipline variable has a positive and significant effect on the work effectiveness of teachers in the Jambur Baru State Madrasah Ibtidaiyah (MIN) Batang Natal Distict. Teamwork (X1) and work discipline (X2) have an effect on work effectiveness as seen from Fcount (10.107) Ftable (3.33) and significant (0.001) < α (0.05). This means that simultaneously it his asignificant effect on the effectiveness of the work of theacers in Jambur Baru State Madrasah Ibtidaiyah (MIN) Batang Natal Distict. R Square indicates the independent variable is 93.2 %, while the rest is influeced by other factors not examined in this study.